# Extensions 1→N→G→Q→1 with N=C22×C6 and Q=C3⋊S3

Direct product G=N×Q with N=C22×C6 and Q=C3⋊S3
dρLabelID
C3⋊S3×C22×C6144C3:S3xC2^2xC6432,773

Semidirect products G=N:Q with N=C22×C6 and Q=C3⋊S3
extensionφ:Q→Aut NdρLabelID
(C22×C6)⋊1(C3⋊S3) = C6×C3⋊S4φ: C3⋊S3/C3S3 ⊆ Aut C22×C6366(C2^2xC6):1(C3:S3)432,761
(C22×C6)⋊2(C3⋊S3) = C2×C324S4φ: C3⋊S3/C3S3 ⊆ Aut C22×C654(C2^2xC6):2(C3:S3)432,762
(C22×C6)⋊3(C3⋊S3) = C6×C327D4φ: C3⋊S3/C32C2 ⊆ Aut C22×C672(C2^2xC6):3(C3:S3)432,719
(C22×C6)⋊4(C3⋊S3) = C2×C3315D4φ: C3⋊S3/C32C2 ⊆ Aut C22×C6216(C2^2xC6):4(C3:S3)432,729
(C22×C6)⋊5(C3⋊S3) = C23×C33⋊C2φ: C3⋊S3/C32C2 ⊆ Aut C22×C6216(C2^2xC6):5(C3:S3)432,774

Non-split extensions G=N.Q with N=C22×C6 and Q=C3⋊S3
extensionφ:Q→Aut NdρLabelID
(C22×C6).1(C3⋊S3) = C626Dic3φ: C3⋊S3/C3S3 ⊆ Aut C22×C6363(C2^2xC6).1(C3:S3)432,260
(C22×C6).2(C3⋊S3) = C2×C32⋊S4φ: C3⋊S3/C3S3 ⊆ Aut C22×C6183(C2^2xC6).2(C3:S3)432,538
(C22×C6).3(C3⋊S3) = C3×C6.7S4φ: C3⋊S3/C3S3 ⊆ Aut C22×C6366(C2^2xC6).3(C3:S3)432,618
(C22×C6).4(C3⋊S3) = A4⋊Dic9φ: C3⋊S3/C3S3 ⊆ Aut C22×C61086-(C2^2xC6).4(C3:S3)432,254
(C22×C6).5(C3⋊S3) = C62.10Dic3φ: C3⋊S3/C3S3 ⊆ Aut C22×C6108(C2^2xC6).5(C3:S3)432,259
(C22×C6).6(C3⋊S3) = C2×C9⋊S4φ: C3⋊S3/C3S3 ⊆ Aut C22×C6546+(C2^2xC6).6(C3:S3)432,536
(C22×C6).7(C3⋊S3) = C2×C32.3S4φ: C3⋊S3/C3S3 ⊆ Aut C22×C654(C2^2xC6).7(C3:S3)432,537
(C22×C6).8(C3⋊S3) = C6210Dic3φ: C3⋊S3/C3S3 ⊆ Aut C22×C6108(C2^2xC6).8(C3:S3)432,621
(C22×C6).9(C3⋊S3) = C624Dic3φ: C3⋊S3/C32C2 ⊆ Aut C22×C672(C2^2xC6).9(C3:S3)432,199
(C22×C6).10(C3⋊S3) = C2×He37D4φ: C3⋊S3/C32C2 ⊆ Aut C22×C672(C2^2xC6).10(C3:S3)432,399
(C22×C6).11(C3⋊S3) = C3×C625C4φ: C3⋊S3/C32C2 ⊆ Aut C22×C672(C2^2xC6).11(C3:S3)432,495
(C22×C6).12(C3⋊S3) = C62.127D6φ: C3⋊S3/C32C2 ⊆ Aut C22×C6216(C2^2xC6).12(C3:S3)432,198
(C22×C6).13(C3⋊S3) = C22×C9⋊Dic3φ: C3⋊S3/C32C2 ⊆ Aut C22×C6432(C2^2xC6).13(C3:S3)432,396
(C22×C6).14(C3⋊S3) = C2×C6.D18φ: C3⋊S3/C32C2 ⊆ Aut C22×C6216(C2^2xC6).14(C3:S3)432,397
(C22×C6).15(C3⋊S3) = C63.C2φ: C3⋊S3/C32C2 ⊆ Aut C22×C6216(C2^2xC6).15(C3:S3)432,511
(C22×C6).16(C3⋊S3) = C23×C9⋊S3φ: C3⋊S3/C32C2 ⊆ Aut C22×C6216(C2^2xC6).16(C3:S3)432,560
(C22×C6).17(C3⋊S3) = C22×C335C4φ: C3⋊S3/C32C2 ⊆ Aut C22×C6432(C2^2xC6).17(C3:S3)432,728
(C22×C6).18(C3⋊S3) = C22×He33C4central extension (φ=1)144(C2^2xC6).18(C3:S3)432,398
(C22×C6).19(C3⋊S3) = C23×He3⋊C2central extension (φ=1)72(C2^2xC6).19(C3:S3)432,561
(C22×C6).20(C3⋊S3) = C2×C6×C3⋊Dic3central extension (φ=1)144(C2^2xC6).20(C3:S3)432,718

׿
×
𝔽